Rhyme and Rhyming in Verbal Art, Language, and Song - Sykäri, Venla; Fabb, Nigel (Studia Fennica Folkloristica, 2022)
This collection of thirteen chapters answers new questions about rhyme, with views from folklore, ethnopoetics, the history of literature, literary criticism and music criticism, psychology and linguistics. The book examines rhyme as practiced or as understood in English, Old English and Old Norse, German, Swedish, Norwegian, Finnish and Karelian, Estonian, Medieval Latin, Arabic, and the Central Australian language Kaytetye. Some authors examine written poetry, including modernist poetry, and others focus on various kinds of sung poetry, including rap, which now has a pioneering role in taking rhyme into new traditions. Some authors consider the relation of rhyme to other types of form, notably alliteration. An introductory chapter discusses approaches to rhyme, and ends with a list of languages whose literatures or song traditions are known to have rhyme.